Increasing innovation and digital marketing in the batu brush business, Pererenan Village, Bali - Ni Made Dwi Puspitawati; Ni Kadek Purnadewi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The creative industry is one of the sectors affected by the Covid-19 pandemic. One way to win the competition is to implement a product innovation strategy that can attract consumers and have a competitive advantage for SMEs. Batu Brush is one of the SMEs that sells various kinds of brush stone products so far has experienced various problems, including: (1) marketing is still conventional, (2) stone brush motifs that have so far lacked innovation. The community service program carried out is to provide education to Batu Brush business owners about the importance of using social media such as Instagram to increase sales turnover through promotions, as well as helping Batu Brush business owners about product innovation, for example creating new image motifs. The method used is counselling about digital marketing through social media Instagram and socialization about the application of new motifs for the diversity of motifs owned by Batu Sikat SMEs. The results of this activity are where partners can implement digital marketing so that the market share is wider and partners can implement product innovations with a variety of motifs that can become selling points and high competitiveness so that in the end it is hoped that Batu Sikat SMEs can increase their turnover.